Depopulation, the new opportunity for information professionals - Sanz-Martos, Sandra (Anuario ThinkEPI, 2021)
Depopulation is one of the most important challenges we face as a society. El Plan de medidas ante el reto demográfico of the Ministerio de Transformación Ecológica y Reto Demográfico is structured around ten lines of action including 130 measures. Among these ten, numbers 2, 3, 6, and 9 stand out in terms of the potential for a greater contribution by information professionals. As experts in digital transformation and skills, innovation, and entrepreneurship as well as promoters of culture, we cannot miss this opportunity to present ourselves as ideal candidates to lead these measures.
Keywords: Depopulation; Demographic challenge; Digital skills; Information professionals; Cultural promotion; Professional opportunities